2021
DOI: 10.1002/pd.5900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of three carrier screening workflows designed to identify at‐risk carrier couples

Abstract: Objective: To evaluate the efficacy of three different carrier screening workflows designed to identify couples at risk for having offspring with autosomal recessive conditions.Methods: Partner testing compliance, unnecessary testing, turnaround time, and ability to identify at-risk couples (ARCs) were measured across all three screening strategies (sequential, tandem, or tandem reflex).Results: A total of 314,100 individuals who underwent carrier screening were analyzed. Sequential, tandem, and tandem reflex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For example, research has shown that tandem reflex screening, compared with sequential screening, improves partner testing adherence up to fourfold and still avoids unnecessary partner testing in pregnant patients with negative screen results. 13 Second, there is a shortage of genetic counselors, so workforce constraints must be taken into consideration as tandem testing programs are implemented. Third, given gestational age–based limits to and restrictions on abortion in some states after the Dobbs v Jackson Women's Health Organization ruling, some clinicians and insurance companies might view the loss of abortion access as a reason to restrict prenatal genetic testing.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…For example, research has shown that tandem reflex screening, compared with sequential screening, improves partner testing adherence up to fourfold and still avoids unnecessary partner testing in pregnant patients with negative screen results. 13 Second, there is a shortage of genetic counselors, so workforce constraints must be taken into consideration as tandem testing programs are implemented. Third, given gestational age–based limits to and restrictions on abortion in some states after the Dobbs v Jackson Women's Health Organization ruling, some clinicians and insurance companies might view the loss of abortion access as a reason to restrict prenatal genetic testing.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Genetic carrier screening is genetically and ethically complex. An important clinical counseling consideration is that 70% of individuals will be “screen positive” for one or more genetic conditions and that 1 in every 40 couples will test positive for the same genetic condition using an expanded carrier screening platform 26,99,100 . Some personal considerations for early embryo‐fetal identification, using the expanded genetic carrier screen, would include that some genetic conditions have improved childhood outcomes with early intervention, some carry a risk for childhood intellectual disability, and some will have limited or no treatment options for the fetus/child 101‐103 …”
Section: Resultsmentioning
confidence: 99%
“…An important clinical counseling consideration is that 70% of individuals will be "screen positive" for one or more genetic conditions and that 1 in every 40 couples will test positive for the same genetic condition using an expanded carrier screening platform. 26,99,100 Some personal considerations for early embryo-fetal identification, using the expanded genetic carrier screen, would include that some genetic conditions have improved childhood outcomes with early intervention, some carry a risk for childhood intellectual disability, and some will have limited or no treatment options for the fetus/child. [101][102][103] Direct to consumer medical testing for disease risk has created new questions, expectations, and concerns for the medical provider, who did not order the test or provide any risk-benefit counseling for patient/couple's informed consent.…”
Section: Preconception Screeningmentioning
confidence: 99%
“…Several factors appear to influence the likelihood of partner testing completion, including disease severity for the positive result (Jurgensmeyer et al, 2021;Shapiro et al, 2021) and presence of the partner at the initial ECS appointment (Jurgensmeyer et al, 2021). While some individuals may decline partner testing as the information would not change their reproductive management, prior studies have identified this attitude is generally held by a minority (33.3%) of patients (Shapiro et al, 2021) (Arjunan et al, 2021).…”
Section: Perceived Barriers To Ecsmentioning
confidence: 99%